The role of kiai and nyai in grounding the values of al-Qur'an education in rural communities - Arifin, Zainal; Rohmaniyah, Vivid; Mahmud, Salami; Hanif, Muhammad (UIN Ar-Raniry Banda Aceh, 2026)
Qur'an education has a fundamental role in shaping the character of rural communities. In Indonesia, this central role is carried out collaboratively by kiai and nyai. This article aims to analyze their dual role in grounding the values of the Qur'an, that is, transforming it into a practical guideline for life. The background of this research departs from the lack of literature that comprehensively examines the role of nyai, which is often overlooked, despite its very vital contribution to the education of women and children. The research method used is qualitative with a case study approach. Data were collected through in-depth interviews, participatory observations, and documentation studies in Godog village, Laren District, Lamongan Regency. The results of the study show (1) the collaborative role of Kiai and Nyai. They carry out complementary roles. The kiai, as a formal leader, is responsible for the teaching of theoretical sciences such as tafsir and fiqh. Meanwhile, Nyai focuses on informal education, teaching the reading and writing of the Qur’an. The collaboration creates a holistic education system. (2) Customary teaching methods in Qur'an Education: Qur'an education carried out by kiai and nyai in rural taklim assemblies has a prominent characteristic. (3) The impact of kiai and nyai on the morality and character of the community. The impact can be seen from the formation of an honest, tolerant, and simple community character. This study concludes that the synergy of kiai and nyai is the key to the success of Qur'an education in rural areas.